2021
DOI: 10.1038/s41598-021-82109-3
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality video game improves high-fidelity memory in older adults

Abstract: Therapeutic interventions have not yet been shown to demonstrate restorative effects for declining long-term memory (LTM) that affects many healthy older adults. We developed a virtual reality (VR) spatial wayfinding game (Labyrinth-VR) as a cognitive intervention with the hypothesis that it could improve detailed, high-fidelity LTM capability. Spatial navigation tasks have been used as a means to achieve environmental enrichment via exposure to and learning about novel and complex information. Engagement has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…Prior research in our lab and others has demonstrated positive effects of large, immersive 3D video game playing on hippocampal-based memory ability (Clemenson and Stark, 2015;Clemenson et al, 2019Clemenson et al, , 2020Wais et al, 2021). For example, in an intervention using young non-gamer adults, we found that 2 weeks of playing Super Mario 3D World improved hippocampal-based memory performance relative to both active and no-contact control groups (Clemenson and Stark, 2015), with the amount of exploration in the game correlating with the amount of improvement.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…Prior research in our lab and others has demonstrated positive effects of large, immersive 3D video game playing on hippocampal-based memory ability (Clemenson and Stark, 2015;Clemenson et al, 2019Clemenson et al, , 2020Wais et al, 2021). For example, in an intervention using young non-gamer adults, we found that 2 weeks of playing Super Mario 3D World improved hippocampal-based memory performance relative to both active and no-contact control groups (Clemenson and Stark, 2015), with the amount of exploration in the game correlating with the amount of improvement.…”
Section: Introductionmentioning
confidence: 49%
“…The present study sought to determine whether playing Minecraft would improve memory function in middle-aged adults in the way it has improved memory function in younger adults (Clemenson et al, 2019) and in the way other video games centered on exploration and with large amounts of novelty have improved memory ability in both younger (Clemenson and Stark, 2015) and older (Clemenson et al, 2020;Wais et al, 2021) adults. The results were remarkably consistent with our prior work (Figure 3) and the work of others (Wais et al, 2021). Even modest amounts of gameplay (e.g., 30 min/day over 2-4 weeks) improved performance on a hippocampal dependent memory task while not affecting a simpler recognition memory task that is far less reliant upon the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is solid evidence that visual-and motor-related processes influence memory (Maguire et al, 2003;Madan and Singhal, 2012a,b). Considering that the hippocampus plays a central role in both long-term memory and spatial navigation (e.g., Rolls and Xiang, 2006), it is possible to enhance memory (also for therapeutic interventions) through the experience of enriched environments administered through videogames and virtual reality (Clemenson and Stark, 2015;Mishra et al, 2016;Wais et al, 2021).…”
Section: Virtual Reality and Memorymentioning
confidence: 99%
“…The use of virtual reality to enhance memory is also an emerging method in neuroscience research (Mishra et al, 2016;Wais et al, 2021). Evidence shows that memory processes involve spatial navigation, that is to say, superior memorizers tend to associate specific information to specific places, requiring a visual-motor experience (Maguire et al, 2003;Buzsáki and Moser, 2013;Hartley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that cognitive interventions using closed-loop, adaptive algorithms 41 designed to target specific cognitive abilities in older adults can improve task performance and neural measures of cognition 12,23,[42][43][44] . These interventions, delivered as engaging video games, have shown positive effects not only with older adults, but in diverse populations [45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%